Evaluation of anti-thyroglobulin antibodies and thyroid stimulating hormone level in cases of recurrent early pregnancy loss - Elmahdy, Mohamed; Elsayed, Eman T. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Autoimmune thyroid disease (AITD) is by far the most frequent cause of hypothyroidism in women in reproductive age. The prevalence of hypothyroidism in the general population of reproductive age is 2-3%. The objective of this study was to evaluate maternal anti-thyroglobulin (ATG) concentrations and thyroid stimulating hormone (TSH) level in cases of recurrent miscarriage. Methods: 200 female patients divided into two groups. Group A: 100 female patients with history of recurrent miscarriage. Group B: 100 female patients with at least 2 living children and without history of recurrent early miscarriage. Antithyroglobulin antibodies using chemilumeniscence immunoassay (normal level up to 115 IU/ml) and TSH level using chemilumeniscence immunoassay (normal level 0.350-2 U/ml) were assessed. Results: 8.0% of cases (n = 100) and 2.0% of control group (n = 100) were positive for anti TG antibodies. There was no significant relationship between the presence of anti TG antibodies and RPL (p = 0.052). 19% of cases (n = 100) were positive for TSH level. On the other hand, 14% of control group (n = 100) were positive for TSH level there was no significant relation between recurrent pregnancy loss and TSH, (P = 0.34). Conclusions: Neither TSH nor ATG showed significant difference in cases with recurrent miscarriage.